Pengaruh Fee Audit, Audit Tenure, dan Spesialisasi Auditor Terhadap Kualitas Audit: Studi Empiris pada Perusahaan Manufaktur di BEI 2017-2021 - Salsabila, Resti; Erinos, Erinos (Jurnal Nuansa Karya Akuntansi, 2023)
This study aims to prove the effect of audit fees, audit tenure and educational specifications on audit quality in manufacturing companies in the Indonesian capital market. The sample size used was 44 companies. The data used is from 2017 to 2021, so the total amount of data processed is 220 observations. The data is obtained from the annual report published by the Indonesia Stock Exchange. The analytical method used is multiple regression while testing the hypothesis is done by statistical t-test. In accordance with the results of hypothesis testing, it was found that fee audits and education specifications individually have a positive and significant effect on audit quality in manufacturing companies on the Indonesia Stock Exchange, while tenure audits have no significant effect on audit quality in manufacturing companies on the Indonesia Stock Exchange from 2017 to 2021.